Struktur Tor Tor Usihan Bodat Haudanan dalam Pesta Rondang Bittang pada Masyarakat Simalungun - Tesya Sandrina; Tuti Rahayu; Sitti Rahmah (Universitas Negeri Medan, 2026)
Tor-tor Usihan Bodat Haudanan is a folk dance performed at the Rondang Bittang Festival, a Simalungun community celebration during the harvest. This research aims to analyze the structure of this dance using Anya Peterson Royce's structural theory, which describes the relationship between the parts of the dance. The method used was descriptive qualitative, implemented at the Pematang Raya State Vocational School for Arts and Culture. The results of the research showed that there was an organizational relationship between the beginning, content and conclusion. The first part begins with a gesture of respect to the audience. The main part depicts a monkey stealing fruit in the field, while the ending shows the monkey confused when the rain comes, ending with a tribute. The three acts reflect the relationship between theme, movement and floor patterns. Dynamic dance movements involve the hands, feet and body, inspired by nature and everyday life. This Tor-tor theme reflects the disturbances faced by farmers during the farming process. Music functions as a rhythm that accompanies every movement.